The Effect of Islamic Giving Behavior on Psychological Well-Being through Dopaminergic Mechanisms - Liza Zulfatun Nafi’ah; Moch Taufiq Ridho (West Science Islamic Studies, 2026)
Islamic giving behavior, such as zakat, infaq, alms, and waqaf, possesses not only theological dimensions but also significant impacts on psychological well-being. This study aims to analyze Islamic giving behavior as a psychospiritual strategy to increase dopamine production as a happiness hormone. The method employed in this study was a library study of latest psychospiritual literature. The results show that sharing activities based on spiritual sincerity trigger activity in the brain's reward system, specifically the Ventral Tegmental Area (VTA). This psychospiritual process stimulates the release of dopamine, which elicits feelings of happiness, calm, and meaning (a helper's high). In conclusion, Islamic giving behavior is an effective psychospiritual intervention for increasing subjective happiness through neurobiological mechanisms. This research has implications for the integration of Islamic psychology and neuroscience in strengthening public mental health.